Massive open online courses for building statistical capacity in computer-assisted surveys - Roque, Jude David; Lapitan, Pamela; Pipon, Dave; Rao, Lakshman Nagraj; Durante, Anna Christine; Gentile, Elisabetta ([Manila] Asian Development Bank, 2020)
This brief explains how massive open online courses (MOOCs) can be used to build capacity among statistics professionals in computer-assisted personal interviewing (CAPI).
Keywords: Computer conferencing -- Computer programs; Videoconferencing; Electronic books